"How can I tell?" Consequences of HIV status disclosure among couples in eastern African communities in the context of an ongoing HIV "test-and-treat" trial. (2nd June 2016) - Maeri, Irene; El Ayadi, Alison; Getahun, Monica; Charlebois, Edwin; Akatukwasa, Cecilia; Tumwebaze, Dennis; Itiakorit, Harriet; Owino, Lawrence; Kwarisiima, Dalsone; Ssemmondo, Emmanuel; Sang, Norton; Kabami, Jane; et al.
ABSTRACT: People living with HIV/AIDS anticipate HIV-related stigma and fear disclosure to intimate partners. Yet, disclosure is critical to reducing HIV transmission and improving care engagement. This qualitative study characterized HIV disclosure experiences and normative beliefs among couples in communities participating in an HIV test-and-treat trial in Kenya and Uganda (Sustainable East Africa Research in Community Health, NCT#01864603). In-depth interviews were conducted with care providers ( n = 50), leaders ( n = 32) and members ( n = 112) of eight communities. Data were analyzed using grounded theoretical approaches and Atlas.ti software. Findings confirmed gender differences in barriers to disclosure: while both men and women feared blame and accusation, women also feared violence and abandonment ("I did not tell my husband because [what if] I tell him and he abandons me at the last moment when I am in labor?"). Positive consequences included partner support for increased care-seeking and adherence ("My husband keeps on reminding me 'have you taken those drugs?'") Yet negative consequences included partnership dissolution, blame, and reports of violence ("some men beat their wives just because of that [bringing HIV medications home]"). Among HIV-infected individuals in discordant relationships, men more often reported supportive spouses ("we normally share [HIV-risk-reduction strategies] since I have been infected and she is HIV negative"), than did women ("my husband refused to use condoms and even threatened to marry another wife"). Care providers lent support for HIV-positive women who wanted to engage partners in testing but feared negative consequences: "They engaged the two of us in a session and asked him if we could all test." Findings demonstrate differing experiences and support needs of women and men living with HIV in eastern Africa, with HIV-positive women in discordant couples particularly vulnerable to negative consequences of disclosure. Efforts to strengthen capacity in health systems for gender-sensitive clinician- or counselor-assisted disclosure should be accelerated within test-and-treat efforts.